2018
DOI: 10.1038/s41467-018-03160-9
|View full text |Cite
|
Sign up to set email alerts
|

An unusual type of polymorphism in a liquid crystal

Abstract: Polymorphism is a remarkable concept in chemistry, materials science, computer science, and biology. Whether it is the ability of a material to exist in two or more crystal structures, a single interface connecting to two different entities, or alternative phenotypes of an organism, polymorphism determines function and properties. In materials science, polymorphism can be found in an impressively wide range of materials, including crystalline materials, minerals, metals, alloys, and polymers. Here we report on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
68
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 28 publications
11
68
0
Order By: Relevance
“…Interestingly, the HNF phase is the only phase observed on cooling. On heating, however, an additional phase is formed in an ≈14 °C temperature interval above the HNF phase, which is characterized by thin‐film textures typically observed for oblique columnar (Col ob ) phases (Figure b) . DSC measurements performed for both compounds, ( m R , p S )‐ 5 and ( m S , p R )‐ 5 , performed at the same heating/cooling rate (5 °C min −1 , see Figure S4 in the Supporting Information), confirm the number of phase transitions on heating and cooling, respectively.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Interestingly, the HNF phase is the only phase observed on cooling. On heating, however, an additional phase is formed in an ≈14 °C temperature interval above the HNF phase, which is characterized by thin‐film textures typically observed for oblique columnar (Col ob ) phases (Figure b) . DSC measurements performed for both compounds, ( m R , p S )‐ 5 and ( m S , p R )‐ 5 , performed at the same heating/cooling rate (5 °C min −1 , see Figure S4 in the Supporting Information), confirm the number of phase transitions on heating and cooling, respectively.…”
Section: Resultssupporting
confidence: 52%
“…The synthetic approach for the new compounds ( m R , p S )‐ 5 and ( m S , p R )‐ 5 (Figure ) was described earlier, and involved the stepwise deprotection and esterification of mono‐tetrahydropyranyl (THP)–mono‐ tert ‐butyldimethylsilyl (TBDMS)‐protected 3,4′‐dihydroxybiphenyl, which was synthesized by a Suzuki coupling reaction (for the synthesis scheme and characterization data, see Scheme S1 as well as Figures S1 and S2 in the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,68] A close relationship between HNF and DC phases was recently highlighted by showing that a spatially confined sample can exhibit both morphologies, depending solely on the diameter of the channels into which the material was introduced. [69] Since then, several groups reported use of FFTEM, low dose thin film TEM, [70] SEM, [71] and AFM [65,72] techniques in the investigation of the structure of supramolecular assemblies of bent and oligomeric molecules (Figure 3b-d), leading to a quickly growing number of reports on the identification of related phases. It was found that helical nanofilament phases may exhibit either very short (helical nanocrystallite phase, HNC, Figure 3a), [73] or much longer fibers (helical microfilament phase, HµF).…”
Section: Liquid Crystals With Chiral Morphologiesmentioning
confidence: 99%
“…Polymorphism of liquid crystals of a bent-core-type molecule controlled solely by cooling speed. [86] This research bridges DNA origami technology with a high programmable capability of unit structure and chirality-controlled materials and colloidal science, which would have important contributions in DNA-based nanoarchitectonics. [93] In soft and flexible liquid-crystalline materials, factors to induce chirality in entire materials are not limited in the range of directly interacting vicinities.…”
Section: Chirality In Liquid Crystalsmentioning
confidence: 99%